The Jesuit series. - Dimler, G. Richard, 1931-; Daly, Peter M. (Peter Maurice) (University of Toronto Press, 2002)
The Corpus Librorum Emblematum (CLE) Series presents documentation relating to printed books belonging to the tradition of emblems and imprese. The individual catalogues provide comprehensive short-title information accompanied by facsimile reproductions of title pages, and where possible also a sample emblem. The volumes also provide a representative selection of library locations and press marks. Finger prints and facsimile title-pages enhance the bibliographic description of the books so that the record provided by CLE contains sufficient information to identify the edition or issue of a given emblem book. The bibliography encompasses all extant books of emblems, works illustrated with emblems, and books dealing with the theory and practice of emblematics written by members of The Society of Jesus. Translations and adaptations of Jesuit works in all languages are also included. The complete Jesuit Series will comprise some 1,700 entries: about 500 first editions, and a further 1,200 subsequent editions, issues and translations.
Keywords: Jesuits -- Bibliography.; Jesuits; Emblem books -- Bibliography.; Emblems -- Bibliography.; Livres à figures -- Bibliographie.; Emblèmes -- Bibliographie.; REFERENCE -- Bibliographies & Indexes.; DESIGN -- Book.; Emblem books; Emblems; Bibliographies